Parents Education and Oral Health Care in Early Childhood Caries prevention In Varamin City; Iran: A Cross Sectional Study - Hatami, Hossein; Ghorbani, Zahra; Deghatipour, Marzie; Ghazizadeh Ahsaie, Mitra (Journal of Dental School, 2018)
Objectives Oral health is a major component of overall health improvement and well-being. A large number of children are suffering from Early Childhood Caries (ECC). Parental knowledge and level of education can improve their child’s oral health care leading to reduction of ECC incidence. The aim of this study was to evaluate the level of education and knowledge in a group of parents, having three year old children, on ECC occurrence. Methods A total of eight hundred and fifteen, three-year-old children were recalled using pregnancy records available in healthcare centers of Varamin city, Iran. Dental examinations were performed by two calibrated senior dental students using decayed missed filled teeth (dmft) index using WHO standard method available. Parents’ knowledge, level of education and their opinion on their child/children‘s oral health care were recorded using WHO questionnaire. An independent T-test, Chi-square test and zero inflated Poisson regression was applied for statistical analysis. Results The mean dmft was 2.69 (±3.492, range 0-19) while 43.4% were caries free. In total, 85% of parents had high levels of education (above high school diploma) and 15% had low levels of education (bellow high school diploma) including illiterates. Children of parents with higher level of education, experienced less dental caries although this difference was not significant (p>0.05). Conclusion More than half of the three-year-old children living in Varamin city had some degrees of dental caries. Dental caries experience among participating children was rather high, despite most parents were educated.